RHINITIS IN INFANTS - S.I. Erdes; N.M. Leonovskaya ("Paediatrician" Publishers LLC, 2009)
The anatomic and physiological peculiarities of upper airways in infants are discussed in this article, and the necessity of its normal functioning in child's organism. Authors give Russian practical rhinitis classification, which is used in pediatric practice. The article gives a detailed description of stages and peculiarities of clinical course of rhinitis in infants, and also shows the principles of treatment and modern approaches to the therapy of patients with rhinitis. Key words: infants, rhinitis, treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):106-110)